THE INFLUENCE OF ENVIRONMENTAL FACTORS ON THE ORGANISM DEPENDING ON AGE (American Journal of Research in Humanities and Social Sciences, 2024)
This paper explores the complex relationships between environmental factors and age-related health outcomes by examining how different stages of life affect susceptibility to environmental risks. Factors such as environmental pollution, climate changeability and lifestyle choices can have a significant impact on the human body, which can have different effects depending on age. By analysing the correlation between environmental exposure and age-related changes in physiology and vulnerability to disease, this study aims to fully understand how individuals at different stages of life are exposed to the environment.